2006
DOI: 10.1007/s11420-006-9018-z
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic Neuropathy: Case Report and Discussion of the Literature on Postoperative Sciatic Neuropathy and Sciatic Nerve Tumors

Abstract: Sciatic nerve injury and dysfunction is not an uncommon cause of lower extremity symptoms in a musculoskeletal practice. We present the case of a man who presented with lower extremity weakness, pain, and cramps, and was initially diagnosed at an outside institution with bilateral S1 radiculopathies and recommended for spine surgery. He came to us for a second opinion. Electrodiagnostic testing revealed an isolated sciatic neuropathy and the patient was referred for imaging, which showed a sciatic nerve sheath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 55 publications
0
19
0
4
Order By: Relevance
“…2016;6(5-6):118-123 sensory symptoms and had normal sural and plantar sensory nerve conduction. In general, peripheral nerve or nerve plexus disorders present with abnormal findings in sensory nerve conduction studies, while disorders involving lesions proximal to the dorsal root ganglion (e.g., myeloradiculopathy) show normal findings in sensory nerve conduction studies [4,5]. The fact that our patient had normal right sural and plantar sensory nerve conduction suggested that the lesion was proximal to the dorsal root ganglion, and the absence of sensory symptoms suggested that the patient's symptoms were associated with an etiology different from that of entrapment or a tumor affecting the first sacral nerve.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…2016;6(5-6):118-123 sensory symptoms and had normal sural and plantar sensory nerve conduction. In general, peripheral nerve or nerve plexus disorders present with abnormal findings in sensory nerve conduction studies, while disorders involving lesions proximal to the dorsal root ganglion (e.g., myeloradiculopathy) show normal findings in sensory nerve conduction studies [4,5]. The fact that our patient had normal right sural and plantar sensory nerve conduction suggested that the lesion was proximal to the dorsal root ganglion, and the absence of sensory symptoms suggested that the patient's symptoms were associated with an etiology different from that of entrapment or a tumor affecting the first sacral nerve.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, pain and dysesthesia are the most common symptoms in the earliest phases of entrapment [3]. A previous case report of a tumor along the sacral nerve passing through the first left pelvic sacral foramen indicated the presence of clear sensory symptoms (pain worsened by movement), atrophy of the innervated muscles, and loss of sensory nerve action potentials in the left sural nerve [4]. The patient in our case had a lesion in a similar location that progressed to atrophy; however, our patient did not exhibit A Case Report of Anterior Horn Disease J Neurol Res.…”
Section: Discussionmentioning
confidence: 99%
“…Sciatica is most commonly caused by herniated disc compressing the nerve roots or lumbosacral degenerative pathology, although very infrequent entrapment of sciatic nerve along its course within the pelvis or the lower extremity due to heterotopic ossification, misplaced intramuscular injections, myofascial bands in the thigh, myositis ossificans of biceps muscle, posttraumatic or anticoagulant-induced hematomas, compartment syndrome, and bone and soft tissue tumors can cause sciatica [3–5]. …”
Section: Discussionmentioning
confidence: 99%
“…If the short head of the biceps femoris is involved, then the lesion is in the proximal to midthigh as the nerve branch of the common peroneal component to the short head of the biceps femoris arises approximately 15 cm proximal to the lateral tibial condyle (25). Cases of sciatic neuropathy often involve the distal tibial nerve innervated muscles and the hamstrings; however, the hamstrings may be partially or completely spared if the lesion is distal to the takeoff of their muscular branches ial nerve suggests a sciatic neuropathy (21,22). In radiculopathy, motor nerve conduction studies may be normal or abnormal depending on the extent of nerve injury (23).…”
Section: Nerve Conduction Studiesmentioning
confidence: 99%
“…displaced components, and transection (Fig 13). There is some thought that underlying spine pathologic conditions make the sciatic nerve more susceptible to traction injury during surgery (22). Postsurgical inflammatory neuropathy, or preferentially descend into the DPN (74).…”
Section: Common Peroneal Neuropathymentioning
confidence: 99%